"BECAUSE WE ALSO HAVE OUR RIGHTS”: PHYSICAL-SPATIAL TRANSFORMATION WITH CHILDREN FROM MORRO DO PAPAGAIO - Mariana Protázio Santos; Paula Barros; Marcela Rodrigues de Almeida Sanches; Anna Pires Diniz (Mix Sustentável)
Although child participation in decision-making is a recognized right, children are often excluded from decision-making processes that will affect the quality of their lives, including those related to urban issues. In the Brazilian context, there is a lack of studies aimed at understanding child participation in the transformation of public spaces. This study aims to explore the repercussions of a physical-spatial transformation involving children aged 9 to 10 years, residents of the Morro do Papagaio favela (Belo Horizonte, Brazil). To this end, interviews, photo-elicitation, and participant observation were conducted. Inductive thematic analysis of the data revealed the value of physical-spatial transformation as a practice that enables the exercise of children's rights to participation, sociability, play, freedom, education, use of public spaces, beauty and well-being. Identifying how children experience public spaces in the favela became crucial to understanding how transforming spaces with children can promote their citizenship.